Integrated studio approach to motivate collaboration in design projects - Tessier, Virginie (Design and Technology Education: An International Journal, 2021)
In an attempt to resolve some of the gaps associated with the pedagogical integration of teamwork in design curricula, this article seeks to share a model for learning teamwork skills. This model is the result of a multiple case study methodology based on the learning experiences of 22 design students. Data was collected during various team projects through questionnaires and interviews. In relation to the concept of the zone of proximal development, the coded data was organised by thematic categories and training levels to provide a practical tool to support teaching and assessment practices to encourage the learning of teamwork skills. The proposed model allows for a systemic understanding of teamwork skills that should be acquired during design training to navigate with efficiency and confidence in the collective projects of design’s community of practice. The use of the model promotes the adoption of more complex teamwork dynamics, such as collaboration, enhanced with an integrated pedagogical approach. It also motivates individual action towards collaborative initiatives in the hopes of more coherent teamwork processes.